2013
DOI: 10.2903/j.efsa.2013.3332
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on Dietary Reference Values for fluoride

Abstract: Following a request from the European Commission, the Panel on Dietetic Products, Nutrition and Allergies (NDA) derived Dietary Reference Values (DRVs) for fluoride, which are provided as Adequate Intake (AI) from all sources, including non-dietary sources. Fluoride is not an essential nutrient. Therefore, no Average Requirement for the performance of essential physiological functions can be defined. Nevertheless, the Panel considered that the setting of an AI is appropriate because of the beneficial effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 126 publications
1
28
0
Order By: Relevance
“…As we previously reported [10], there is some controversy regarding recommendations on Adequate Intake (AI) for F since there are no signs of F deficiency which have been identified in humans, and F has no known essential function in human growth and development [115]. Evidence over the last 20 years has demonstrated that the cariostatic effect of F is topical on the tooth surface and ingestion is not required [116–118].…”
Section: Resultsmentioning
confidence: 99%
“…As we previously reported [10], there is some controversy regarding recommendations on Adequate Intake (AI) for F since there are no signs of F deficiency which have been identified in humans, and F has no known essential function in human growth and development [115]. Evidence over the last 20 years has demonstrated that the cariostatic effect of F is topical on the tooth surface and ingestion is not required [116–118].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the Panel considered in its opinion on DRVs for fluoride (EFSA NDA Panel, 2013b) that the setting of an AI was appropriate because of the beneficial effects of dietary fluoride on prevention of dental caries. For infants below six months of age, the Panel concluded in its previous opinion on nutrient requirements and dietary intakes of infants and young children in the European Union (EFSA NDA Panel, 2013a) that a fluoride intake of 0.08 mg/day is adequate for the majority of infants below six months of age.…”
Section: Ai Of Fluoride In Infantsmentioning
confidence: 99%
“…Nutrient requirements and references should be differentiated from recommended intakes because of differences in the methodology for their derivation and their intention. Considering amongst other nutrient goals for a given population, reference values are translated into recommendations for managing nutritional risks (EFSA NDA Panel, 2010g NDA Panel, 2010f, 2010d, 2010a, 2012a, 2013b, 2013c, 2013d and endorsed opinions on DRVs for biotin and pantothenic acid for public consultation (EFSA NDA Panel, 2013g, 2013a.…”
Section: Methodological Considerationsmentioning
confidence: 99%